Hate speech in comments on social media: Towards a critical digital citizenship (Revista Contexto & Educação, 2025)
With internet access becoming increasingly democratic, social practices have gained new contours and daily adherence, building an inevitable “digital world”. Through communication processes produced on social networks, digital discursive performances operated with meanings and effects emerging from/in digital relationships between users. The present reflections are based on the empirical material generated in the study by Ribeiro (2023), which sought to identify and problematize, through online comments generated from posts by female celebrities on the social network TikTok, speeches that fell into the category “hate”, observing the socially produced meanings around digital practice. From the 96 comments on six videos posted on the pages of six female celebrities, the relationship between gender and race can be seen, which threatens white masculinity, permeating intersectionalities that cross ageism, LGBTphobia, misogyny, racism, sexism and fatphobia, or all of these at the same time or in some proportion. This guides a critical digital citizenship that promotes openness and a sense of plurality about what surrounds individuals to see and read digitally, as well as a critical scrutiny of what they will do, subsequently, with the human behind the screen.
Keywords: Digital performances; TikTok; Hateful comments; Online criticality